Strengthening Nadhatul Ulama as Moderate Islam in the Digital Era - Rosidah, Feryani Umi; Faizah, Nur (Jurnal Studi Multidisiplin Qomaruna, 2024)
The era of the digital, millennial, or Industrial Revolution 4.0 presents numerous challenges and intense competition, necessitating not only global competencies but also critical thinking skills. This is particularly important for Muslims (specifically NU members) to avoid alienation and marginalization. This paper aims to analyze the strengthening of the moderate ideology of NU, which boasts the largest following in Indonesia and significantly influences the nation's civilization. NU, as a moderate Islamic movement, adopts an inclusive approach through the wise use of social media and digital technology, its role in education, promotion of digital literacy, combating hoaxes, and participation in interfaith dialogue. Furthermore, NU promotes an understanding of moderate Islam, fosters peace, and fights extremism amidst the rapid advancement of information technology. Moderate Islam is perceived not merely as a religion but as a civilized way of life. The efforts of NU in the past, present, and future must remain dynamic, continuously adapting to the challenges of the times on a global scale, to build a more advanced Indonesia in the future